Life style modification practices and associated factors among hypertensive patients at public hospitals in Ambo Town, Ethiopia, 2023 - Dachasa Dabalo; Delelegn Yilma; Abebe Dechasa (Elsevier, 2024)
Background: Modifiable lifestyle factors can increase or decrease the risk of hypertension. Despite emerging empirical evidence about efficacy of lifestyle modification in blood pressure control, little known and failed to appropriately counsel, hypertensive patients by health professionals on health lifestyle. General objective: The aim of this study is to assess magnitude of lifestyle modification practices and its associated factors among hypertensive patients. Methods: Institution-based cross-sectional study was conducted among 344 hypertensive using systematic random sampling at public hospitals in ambo town from March 1-30, 2023. Data was collected using adapted structured questionnaire by interview. Logistic regression analysis model was fitted the data, no Multicollinearity detected among independent variables, Adjusted Odds Ratio at 95 % confidence interval was used, P-values less than or equal to 0.05 were considered statistically significant. Descriptive statistic (frequency, mean) used to explain the data. Results: The study has high response rate of 96.9 %. About 56.1 %, (95 % CI: [51.3-61.0]) had a good lifestyle modification practice. In this study, being employed (AOR=3.59, 95 % CI: [1.22-10.54]), Good self-efficacy (AOR=2.92, 95 % CI: [1.06-8.02]), Good knowledge (AOR=3.77 95 % CI: [1.81-7.85]), Normal body mass index (AOR=0.22, 95 % CI: [0.064-0.78]), being underweight (AOR=0.12, 95 % CI: [0.022-0.63]) were factors associated with life style modification practice. Conclusion and recommendation: Life style modification practice is low in this study. Employment, knowledge, self-efficacy, and obesity were significantly associated. Recommendations include, promoting lifestyle modifications, and encouraging healthy behaviors.